Understanding performance through organizational culture - Rodrigues, André Filipe Geraldes Barba Fernandes (2019)
Today’s businesses world is characterized by its constant rapidly changing environment, facing a very competitive economic context, making it crucial for business success to understand, timely, what drives its results, namely its performance. Organizational performance may be affected by a several number of variables and the understandment of these variables is decisive for business management. Therefore, this research aims to address and measure organizational performance, understanding if and how much it is influenced by organizational culture, specifically by its types, in case clan culture, adhocracy culture, hierarchy culture and market culture, as well as if employee work engagement mediates the mentioned relationship. That is accomplished through formulation and testing of four research hypotheses. For that purpose we applied a questionnaire, preceded by a pre-test procedure, to a sample composed by security professionals, receiving a total of 629 valid answers, aiming to measure organizational culture through the application of FOCUS questionnaire, based on the competing values framework, as well as employee work engagement through UWES questionnaire and organizational performance through a perceptual organizational performance questionnaire. Our results evidence that more than one organizational culture type positively and significantly influences both organizational performance and employee work engagement, as well as that employee work engagement partially mediates the influence of all organizational culture types on organizational performance.